DOMESTIC VIOLENCE IN COLLEEN HOOVER’S IT ENDS WITH US - Sitorus, Sofia Sahana; Suhendi, Andang (Universitas Islam Sumatera Utara, 2025)
This research examines the portrayal of domestic violence in Colleen Hoover’s novel It Ends with Us, focusing on the experiences of the protagonist, Lily Bloom, who endures various forms of abuse both in her childhood and adulthood. The study identifies four major categories of domestic violence depicted in the narrative—physical, emotional, verbal, and sexual—by employing Tulangow’s theoretical framework on domestic violence. Conducted through a qualitative descriptive method as outlined by Creswell (2012), this study analyzes textual evidence drawn from the novel to understand the psychological, emotional, and social consequences of abuse on the main character. The findings reveal that domestic violence in the novel not only results in physical injuries but also generates long-lasting psychological trauma, fear, anxiety, and diminished self-worth. Furthermore, the narrative exposes the cyclical nature of abuse and its intergenerational impact, especially through Lily’s reflections on her childhood and her concerns about her unborn child. This study demonstrates how literary fiction can serve as a powerful vehicle for raising public awareness of gender-based violence, offering insight into the lived realities of survivors, and prompting critical reflection on emotional resilience, agency, and social intervention.